(untitled) (Research, Society and Development, 2020)
Objective: compare the use of the hot tub with the hygiene bath after invasive procedures. Merhodology: this is an uncontrolled experimental study with a quantitative approach carried out with newborns and infants. Comparative behavioral and vital signs assessment was performed before and after a hygiene bath and with the use of a hot tub. The McNemar test was used, considering a 95% confidence interval. Results: 10 evaluation werw recorded, being 5 from the control group (hygiene bath) and 5 from the experimental group (hot tub). There was an improvement in the behavioral status of newborns and infants after bathing in the hot tub compared to hygiene, a significant difference was noted in the variables: crying (p =0.046) and collaborating passively (p = 0.046). A significant difference in temperature was obtained (p = 0.039). Conclusion: the hot tub bath proved to be a relevant technique for improving vital parameters and improving the behavioral state of the child in the hospitalization process, leaving them calmer and more calm.